Narcotics and Psychotropic Substances: Towards a Contemporary Academic Perspective on Understanding Conceptual Differences in Definitions and Medical and Legal Characteristics within the International and Palestinian National Frameworks - Dr. Khaled Taha Mohammed Abu Thaher (Journal of Scientific and Human Dimensions, 2026)
This study aims to provide a theoretical framework and a contemporary academic perspective for understanding the conceptual differences between drugs and psychotropic substances in their definitions and medical and legal characteristics within both the international and Palestinian national frameworks. The study's central question is: "What are the conceptual differences between drugs and psychotropic substances in their definitions and medical and legal characteristics within the international and Palestinian national frameworks?" The study's significance lies in its clarification of these differences in terms of definitions, medical characteristics, and legal characteristics within both the international and Palestinian national frameworks. The study is divided into three sections:- Section One: Differences between narcotics and psychotropic substances in terms of definitions and classifications- Section Two: Differences between narcotics and psychotropic substances in terms of medical use-Section Three: Conceptual differences between narcotics and psychotropic substances in terms of legal characteristics within the international and Palestinian national frameworksThe study concluded with a set of findings and recommendations, the most important of which are the following: There is a clear conceptual overlap between narcotics and psychotropic substances in terms of definitions, medical effects, and legal characteristics. The study results show that there are significant differences between narcotics and psychotropic substances in terms of definitions, health characteristics, medical uses, and legal characteristics. The study proved that the provisions of the Palestinian Law on Combating Drugs and Psychotropic Substances No. 18 of 2015 are fully consistent with international standards related to combating narcotics and psychotropic substances.One of the most important recommendations is that relevant parties, especially the Palestinian Ministry of Health, develop educational awareness programs based on the distinction between narcotics and psychotropic substances. These programs should be presented to members of the security, media, university, and educational agencies, and to everyone involved in these issues. The study also recommends that the World Health Organization and relevant international organizations develop a unified and international understanding of the differences between narcotics and psychotropic substances in terms of definitions and medical and legal characteristics.
Keywords: Narcotics; psychoactive substances; definitions; medical properties; legal definitions; Palestinian legislation; international law.